Hierarchical unidirectional fluidic solar-electro-thermal evaporator for all-day efficient water purification. (November 2022) - Chu, Z.; Liu, Z.; Li, Z.; Cao, Y.; Tian, X.; Jia, C.; Wang, J.; Wang, D.; Liu, Z.; Huang, W.
Abstract: Constructing a high-efficiency evaporation system with all-day operation capability remains a great challenge for the emerging solar water purification technologies due to the accompanied salt-fouling problem and uncertain natural sunlight conditions. Here, a hierarchical solar-electro-thermal evaporator with serpentine and unidirectional fluidic structure is developed by in situ assembling MoS2 nanosheet arrays on activated Ti mesh to integrate solar-thermal desalination and electro-thermal desalination for all-day efficient clean water production. The serpentine structure serves as controllable current channels for efficient Joule heating, whereas the unidirectional fluidic structure functions as water pathways for manipulating the salt migration. As a result, the fabricated device realizes continuous water extraction from 6.0% of concentrated brine under 3 sun for 8 h without salt accumulation, and the evaporator can achieve extremely high water evaporation rate of 7.88 kg/m 2 /h under solar-electro-thermal mode based on the critical synergistic effect (1 sun-2.0 A). As a proof-of-concept application, the 3D printing desalination system can achieve continuous clean water extraction from seawater and/or wastewater with high production rate of 7.4 kg/m 2 /d and salt ions concentration far below the drinking standards defined by the World Health Organization. Highlights: A hierarchical solar-electro-thermal evaporator is fabricated. The device has excellent salt-resistant in 6.0% of concentrated brine under 3 sun. The evaporator has high rate of 7.88 kg/m 2 /h under solar-electro-thermal mode. Graphical abstract: Image 1